2023
DOI: 10.1002/qj.4442
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aeolus wind lidar observations on the representation of the West African monsoon circulation in the ECMWF and DWD forecasting systems

Abstract: Aeolus is the first satellite mission to acquire vertical profiles of horizontal line‐of‐sight winds globally and thus fills an important gap in the Global Observing System, most notably in the Tropics. This study explores the impact of this dataset on analyses and forecasts from the European Centre for Medium‐Range Weather Forecasts (ECMWF) and Deutscher Wetterdienst (DWD), focusing specifically on the West African Monsoon (WAM) circulation during the boreal summers of 2019 and 2020. The WAM is notoriously ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 89 publications
2
6
0
Order By: Relevance
“…In addition, we demonstrate the existence of an orbital-and altitude-dependent bias in the Rayleigh-clear channel, which is visible with respect to both radiosondes and ECMWF model equivalents. This bias has already been documented by Borne et al (2023) in West Africa using model equivalents and is now confirmed observationally. The underlying cause for this bias, however, remains unknown.…”
Section: Case Studiessupporting
confidence: 71%
See 2 more Smart Citations
“…In addition, we demonstrate the existence of an orbital-and altitude-dependent bias in the Rayleigh-clear channel, which is visible with respect to both radiosondes and ECMWF model equivalents. This bias has already been documented by Borne et al (2023) in West Africa using model equivalents and is now confirmed observationally. The underlying cause for this bias, however, remains unknown.…”
Section: Case Studiessupporting
confidence: 71%
“…2a). This altitude-and orbit-dependent bias was already described by Borne et al (2023) using first-guess departure statistics over West Africa.…”
Section: Rayleigh-clearsupporting
confidence: 52%
See 1 more Smart Citation
“…West winds are accelerated in the equatorial East Pacific. The strengthening of easterlies around the west coast of Africa is probably related to the mid‐level African easterly jet, which was found to be strongly influenced by the Aeolus HLOS winds, especially the northern part (Borne et al ., 2022). Uncertainties in the Indian Ocean are likely to be associated with the synoptic‐scale monsoon circulation system in the lower troposphere, which typically lasts from June to September.…”
Section: Assessment Of Nwp Impact Of Aeolus Hlos Windsmentioning
confidence: 99%
“…Despite the unforeseen signal loss and lower precision, Aeolus winds were assimilated into the ECWMF model through the four‐dimensional variational (4D‐Var) data assimilation technique to improve operational weather forecasts (Rennie et al., 2021). To assess the added value of Aeolus observations to NWP, many institutions have conducted Observing System Experiments (OSEs) with global NWP models, including ECMWF, National Oceanic and Atmospheric Administration (NOAA), Deutscher Wetterdienst (DWD), Météo‐France, Environment and Climate Change Canada, Korean Integrated Model (KIM), etc (Borne et al., 2023; Garrett et al., 2022; Laroche & St‐James, 2022; Lee et al., 2023; Pourret et al., 2022; Rennie et al., 2021). The evaluations demonstrated that with Aeolus data assimilation, the wind vector forecasts are improved by up to 4%, particularly in the upper troposphere and/or lower stratosphere over the tropics and polar regions (Garrett et al., 2022; Laroche & St‐James, 2022; Pourret et al., 2022; Rennie et al., 2021).…”
Section: Introductionmentioning
confidence: 99%